To Lighten the Burden of Cure: Thyroid Disease in Long-Term Survivors After TBI Conditioning for Paediatric ALL - Zubarovskaya, Natalia; Bauer, Dorothea; Ronceray, Leila; Poetschger, Ulrike; Kurzmann, Paulina; Lender, Carina; Kuzmina, Zoya; Lawitschka, Anita (Frontiers in Pediatrics, 2022)
Thyroid disorders are well studied after allogeneic haematopoietic stem cell transplantation (HSCT) following total body irradiation (TBI)-based conditioning, occurring in 15–30% of paediatric survivors. The toxic effect of TBI is known but data on the role of immunological dysregulation (ID) and chronic graft-versus-host-disease (cGvHD) are scarce. We studied functional and structural thyroid disorders in 97 paediatric ALL patients after TBI-based HSCT, assessing their correlation with patient/transplant characteristics including cGvHD, prolonged immunosuppression and ID. The 10- and 15-year cumulative incidence (CI) of functional disorders was 50% and 60%. Univariate analysis revealed TBI in 6 versus 8 fractions (p=0.01), an interval between ALL diagnosis and HSCT <1 year (p=0.038), and the application of ATG (p=0.044) as risk factors. The 10- and 15-year CI of structural disorders was 60 and 80%. No correlation between patient/transplant characteristics and structural disorders was observed. cGvHD, prolonged immunosuppression and additional radiotherapy were not associated with any thyroid disease. We observed a significant correlation between ID and the development of thyroid dysfunction in patients with structural changes (10-year CI: 77% for patients with ID versus 56% without ID, p=0.02). The impact of our results on thyroid follow-up evaluations and the significance of hormonal replacement therapy are discussed.